Urgensi Pendidikan Nilai-nilai Tasawuf bagi Remaja di Era Modern - Junaidi, Junaidi (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Research on the urgency of educating Sufism values for teenagers in the modern era uses a library research approach. This research is important to carry out because the challenges for teenagers in this modern era are so great. This research concludes that by practicing Sufism values in everyday life, teenagers are expected to be able to control negative things. At the same time, the values of Sufism education can inspire teenagers to do positive things both for themselves and others.